Surgery impairs glymphatic activity and cognitive function in aged mice - Kai Chen; Xingyu Du; Melissa A. Chao; Zhongcong Xie; Guang Yang (Molecular Brain)
Abstract Delirium is a common complication in elderly surgical patients and is associated with an increased risk of dementia. Although advanced age is a major risk factor, the mechanisms underlying postoperative delirium remain poorly understood. The glymphatic system, a brain-wide network of perivascular pathways, facilitates cerebrospinal fluid (CSF) flow and supports the clearance of metabolic waste. Impairments in glymphatic function have been observed in aging brains and various neurodegenerative conditions. Using in vivo two-photon imaging, we examined the effects of surgery (laparotomy) on glymphatic function in adult (6 months) and aged (18 months) mice 24 h post-surgery. In adult mice, CSF tracer entry into the brain parenchyma along periarteriolar spaces occurred rapidly following intracisternal tracer injection, with no significant differences between sham and surgery groups. In contrast, aged mice exhibited delayed tracer influx, with further impairments observed in the surgery group compared to sham controls. This glymphatic dysfunction correlated with poorer T-maze performance in aged mice. These findings suggest that surgery exacerbates glymphatic impairment in aging brains, potentially hindering brain waste clearance and contributing to postoperative delirium.